Penerapan Model PBL Untuk Meningkatkan Hasil Belajar Peserta Didik Mata Pelajaran Pendidikan Pancasila Di SMK N 2 Semarang - Fachrudin Dwi Saputro; Supriyono Purwosaputro; Suharmanto Suharmanto (Journal on Education, 2024)
The background of this research is the low learning outcomes of students in Pancasila Education subjects. The aim of this research is to explain how to apply a problem-based learning model to improve student learning outcomes in Pancasila Education subjects. This study uses a qualitative methodology. This type of classroom action research has two cycles, each with one meeting with planning, implementation, observation and reflection activities. The use of problem-based learning models and student learning outcomes are the focus of this research. This research involved 36 students and educators of class XI PM 1 during the odd semester of the 2023/2024 academic year. Data is collected in the form of observations, tests and documentation. This study uses qualitative analysis methods. The results of this research show that both teacher and student activities and student learning outcomes have improved in learning. This research found that teachers and students have more time to study. In cycle I, student learning outcomes were in the poor category, while in cycle II, student learning outcomes were in the good category. The learning outcomes of class XI PM 1 students can be improved by implementing a problem-based learning model in the Cultural Collaboration in Pancasila Education material.